2021
DOI: 10.1177/08948453211022845
|View full text |Cite
|
Sign up to set email alerts
|

Jobs, Careers, and Callings: Exploring Work Orientation at Mid-Career

Abstract: Mid-career is a time when work orientation (i.e., viewing ones’ work as a job, a career, or a calling) comes into sharper focus. Using Wrzeniewski et al.’s tripartite model, we conducted a discriminant function analysis to determine the combination of variables that best discriminates among people who are aligned with a job, a career, or a calling orientation in a sample of 251 full-time, North American mid-career employees. Compared to those who approach work as a job, those with a calling orientation were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
2
5
1
Order By: Relevance
“…Our investigation of the three work orientations also provides insights into culture-specific aspects of the three work orientations. Unlike previous findings using American workers (Mantler et al, 2021; Wrzesniewski et al, 1997), the difference between a job and a career orientation is not as stark as the differences between a calling and the other orientations in this study. The findings may be partly due to cultural differences and an uneven number of participants in each group.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our investigation of the three work orientations also provides insights into culture-specific aspects of the three work orientations. Unlike previous findings using American workers (Mantler et al, 2021; Wrzesniewski et al, 1997), the difference between a job and a career orientation is not as stark as the differences between a calling and the other orientations in this study. The findings may be partly due to cultural differences and an uneven number of participants in each group.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that 58.9% of Mongolian respondents saw themselves as having a career orientation, and 34.0% of them had a calling orientation, and only 7.1% saw themselves as having a job orientation. Similar to prior studies (Mantler et al, 2021; Wrzesniewski et al, 1997), we found that a small portion of participants indicated that the same scores for more than one orientation.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations